2018
DOI: 10.1108/ci-04-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementing lean construction practices in the Kingdom of Saudi Arabia (KSA) construction industry

Abstract: Purpose The purpose of this paper is to identify the barriers to implementing lean construction in the Kingdom of Saudi Arabia (KSA) construction industry and to prioritise the principal factors that constitute these barriers. Design/methodology/approach A literature review was initially used to reveal the global barriers to implementing lean construction. Subsequently, these barriers were incorporated into a structured questionnaire, and a convenience sample of 282 construction professionals in the KSA cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(263 citation statements)
references
References 33 publications
6
227
0
9
Order By: Relevance
“…The term "Last Planner" and "Last Planner System" are also used (Koch et al, 2015;Johansen, 2003). It has been speculated that the application of the LPS is stalled at collaborative planning/collaborative programming and it is viewed only as a scheduling tool in the UK (Sarhan and Fox, 2013;Mossman, 2009). In order to understand the differences and similarities in these practices in the UK, a review was undertaken through literature, observed practice, and interview.…”
Section: Introductionmentioning
confidence: 99%
“…The term "Last Planner" and "Last Planner System" are also used (Koch et al, 2015;Johansen, 2003). It has been speculated that the application of the LPS is stalled at collaborative planning/collaborative programming and it is viewed only as a scheduling tool in the UK (Sarhan and Fox, 2013;Mossman, 2009). In order to understand the differences and similarities in these practices in the UK, a review was undertaken through literature, observed practice, and interview.…”
Section: Introductionmentioning
confidence: 99%
“…These metrics have been criticized because they are often calculated after substantial amount of time at receiving reports from work site [40]. When productivity is measured in this way, areas of low productivity are identified at a later stage and usually substantial damage has been done by then [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lean production is a continuous process, thus requires more commitment from workers. While reviewing the literature, other challenges faced in implementing Lean were mentioned repeatedly, they include: Lack of awareness or understanding, technological problems, supply chain problems, customers uncertainties in demand, lack of top management commitment and support, pressure from customers, lack of common vision, lack of communication, educational issues, financial issue, (Sarhan and Fox, 2013;Abdullah et al, 2009). Other challenges faced when in implementing Lean production include; logistic problem, poor organisation, and absence of delegation to improve the flow of work.…”
Section: Impact Of Lean Practices On Organisational Performancementioning
confidence: 99%